TWO DIMENSIONS OF THE BOLOGNA PROCESS: THE PROBLEM OF QUALITY IN EACH OF THEM - Володимир Луговий; Олена Слюсаренко; Жаннета Таланова (National Academy of Educational Sciences of Ukraine, 2022)
The authors of the article analysed the Bologna process implementation in its two main dimensions in terms of "quality assurance" of higher education. It is found that significant progress has been made in ensuring minimum sufficient quality in the first (internal) dimension "compatibility and comparability". In the second (external) dimension "competitiveness and attractiveness" the progress in achieving the most perfect quality is insignificant and is primarily associated not with the pan-European coordinated Bologna process, but with unique national initiatives to create and support leading universities and their elite associations. It is shown that one of the reasons for the current situation is the Bologna process's inattention to rating mechanisms for evaluating and motivating university activities at higher levels of complexity and excellence, instead focusing on accreditation mechanisms and mass higher education. It is argued that the confirmation and aspiration to competitiveness and attractiveness of the European Higher Education Area (EHEA) in the third decade of the Bologna process (until 2030) in the Rome Ministerial Communiqué (2020) obliges to form a strong pan-European policy of real increase of the global competitiveness of the EHEA with the involvement / development of adequate rating mechanisms and strategies for the development of university leadership. In the context of the dimensions of the Bologna process, Ukraine lacks a national strategy-2 for the creation of leading universities and their elite institutional and sectoral associations, which threatens national security, hinders the formation of conditions for effective post-war recovery of Ukraine on a new, highly intellectual, high-tech and highly motivated basis.